2016
DOI: 10.1021/jacs.5b08657
|View full text |Cite
|
Sign up to set email alerts
|

La-Activated Bicyclo-oligomerization of Acetylene to Naphthalene

Abstract: We report the first example of metal-mediated acetylene bicyclopentamerization to form naphthalene in the gas phase. The bicyclic aromatic compound was observed in a complex with La. The La(naphthalene) complex was formed by the reaction of laser-ablated La atoms with acetylene molecules in a molecular beam source and was characterized by mass-analyzed threshold ionization spectroscopy. The bicyclo-oligomerization reaction occurs through sequential acetylene additions coupled with dehydrogenation. Three interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 37 publications
2
54
0
Order By: Relevance
“…We have recently reported the MATI spectroscopy and formation of the metal-hydrocarbon a) Author to whom correspondence should be addressed: dyang0@uky.edu radicals produced by the lanthanide-mediated C− −C or C− −H bond activation of several small alkenes and alkynes. [40][41][42][43][44][45][46][47][48] Our studies demonstrate that the combination of the MATI spectroscopic measurements with electronic structure calculations is a powerful approach to investigate transient metal-hydrocarbon species.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…We have recently reported the MATI spectroscopy and formation of the metal-hydrocarbon a) Author to whom correspondence should be addressed: dyang0@uky.edu radicals produced by the lanthanide-mediated C− −C or C− −H bond activation of several small alkenes and alkynes. [40][41][42][43][44][45][46][47][48] Our studies demonstrate that the combination of the MATI spectroscopic measurements with electronic structure calculations is a powerful approach to investigate transient metal-hydrocarbon species.…”
Section: Introductionmentioning
confidence: 81%
“…Metal ion-hydrocarbon species are largely investigated by infrared or ultraviolet-visible photodissociation or photoelectron spectroscopy, whereas metal atom-hydrocarbon radicals are mainly studied by resonant two-photon ionization and dispersed fluorescence, [35][36][37][38] Fourier transform microwave, 39 and mass analyzed threshold ionization (MATI) spectroscopy. [40][41][42][43][44][45][46][47][48] Spectroscopic measurements probe state specific energies and structures of short-lived species, which are vital for gaining insight into reaction mechanisms and electronic and structural characteristics for efficient bond activation at metal centers. Such measurements can also be used to test electronic structure calculations, where computations are complicated by possibly multiple low-energy isomers of each metal-containing species and high-density of low-lying electronic states or spin-orbit levels of each isomer.…”
Section: Introductionmentioning
confidence: 99%
“…We have extensively used the DFT/B3LYP method and found that this method generally produced adequate results for spectral and structural assignments of organometallic radicals. [63][64][65][66][67][68][69][70]86 No symmetry restrictions were imposed in initial geometry optimizations, but appropriate point groups were used in subsequent optimizations to help identify electronic symmetries. The geometry of each stationary point was obtained through a relaxed potential energy surface scan along the proposed reaction coordinates.…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
“…Because of low ablation laser power, no La clusters were produced except for very small amounts of La 2 , La 2 C, and La 2 O 1,2 . La oxides could be formed by La reactions with oxygen that is present in the carrier gas as an impurity or by laser vaporization of La oxide impurity in the La rod, [63][64][65][66][67][68][69] whereas the La carbide could be associated with La reactions with the vapor of diffusion pump oil. The mass spectra from the two pentene reactions are essentially the same and show a predominant product La(C 5 H 8 ), a significant amount of La (C 10 H 18 ), and two minor species La(C 2 H 2 ) and La(C 3 H 4 ).…”
Section: Experimental and Computational Methodsmentioning
confidence: 99%
See 1 more Smart Citation